The right leadership to direct environmental aspects in an organization (GEON Journal (Management, Organizations and Business), 2016)
To direct the environmental aspects of an organization, to choose a type of leadership as if it were a menu or secret formula to solve a problem, it would be necessary to analyze some types of leadership. Moral leadership highlights the importance of serving the community, of thinking about the collective well-being as it can be felt in our present day with the theme of improving healthy habits and lifestyles, caring for the environment, social responsibility of improve the quality of life by prioritizing the general interest on the subject (Donaires Sánchez, 2003).With the leadership in values ​​the importance that the leader produces over his followers, provoking changes from the awareness about the importance and the value of the results obtained after the realization of the assigned tasks, this can be related to the responsibility that it has the leader regarding printing on its followers the care towards environmental management, the care of the environment, as a value to organizational objectives, seeking a balance between environmental, social and economic (Nader & Castro Solano, 2007).
Keywords: Leadership; enviromental management; organizations